The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1161/circulationaha.107.745174
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plasma Oxidized Low-Density Lipoprotein Removal on Atherosclerosis

Abstract: Background-Several clinical studies of statin therapy have demonstrated that lowering low-density lipoprotein (LDL) cholesterol prevents atherosclerotic progression and decreases cardiovascular mortality. In addition, oxidized LDL (oxLDL) is suggested to play roles in the formation and progression of atherosclerosis. However, whether lowering oxLDL alone, rather than total LDL, affects atherogenesis remains unclear. Methods and Results-To clarify the atherogenic impact of oxLDL, lectin-like oxLDL receptor 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(106 citation statements)
references
References 54 publications
7
97
0
2
Order By: Relevance
“…Aortas were obtained and evaluated as Oil Red O‐stained areas, as described previously (Ishigaki et al ., 2008). Briefly, the aorta was dissected from surrounding tissues, cut open with the luminal surface facing up, and then immersion‐fixed in 10% neutral buffered formalin.…”
Section: Methodsmentioning
confidence: 99%
“…Aortas were obtained and evaluated as Oil Red O‐stained areas, as described previously (Ishigaki et al ., 2008). Briefly, the aorta was dissected from surrounding tissues, cut open with the luminal surface facing up, and then immersion‐fixed in 10% neutral buffered formalin.…”
Section: Methodsmentioning
confidence: 99%
“…To measure serum oxidized LDL levels, serum levels of lectin-like oxidized LDL receptor-1 (LOX-1) ligand were determined using a sandwich enzymelinked immunosorbent assay (ELISA), as described previously 28) . Serum LOX-1 ligand concentration was normalized to serum total cholesterol concentration (Cholesterol E-test; Wako Pure Chemical).…”
Section: Measurement Of Blood Lipoprotein Profiles and Oxidative Stressmentioning
confidence: 99%
“…In particular, the oxidation of LDL is an important factor in this disease because it increases the expression of adhesion molecules that bind to circulating monocytes triggering the subsequent steps for the formation of lesions (CASÓS et al, 2008;ISHIGAKI et al, 2008;KATO et al, 2009). Therefore, the present study demonstrated that the diets containing pequi did not exert pro-atherogenic effect under these experimental conditions.…”
Section: Animals and Dietsmentioning
confidence: 47%